Brain magnetic resonance imaging pattern and outcome in children with haemolytic‐uraemic syndrome and neurological impairment treated with eculizumab. (10th May 2013) - Gitiaux, Cyril; Krug, Pauline; Grevent, David; Kossorotoff, Manoelle; Poncet, Sarah; Eisermann, Monika; Oualha, Mehdi; Boddaert, Nathalie; Salomon, Remi; Desguerre, Isabelle
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to describe the magnetic resonance imaging (MRI) findings and the neurological and neuropsychological outcomes in paediatric, diarrhoea‐associated haemolytic–uraemic syndrome (D+HUS) with central nervous system impairment treated with eculizumab, a monoclonal antibody. Method The 14‐month single‐centre prospective study included seven children (three males, four females; age range 16mo–7y 8mo; median age 3y 7mo) with typical D+HUS and acute neurological impairment. In the acute phase of the disease, neurological assessment and brain magnetic resonance imaging (MRI), including measurement of the apparent diffusion coefficient (ADC), were performed, and neuropsychological evaluation and brain MRI were also carried out 6 months after disease onset. Results In the acute phase, basal ganglia and white matter abnormalities with ADC restriction were a common and reversible MRI finding. In all the surviving patients (5/7), follow‐up MRI after 6 months was normal, indicating reversible lesions. Clinical and neuropsychological evaluations after 6 months were also normal. Interpretation This specific brain MRI pattern consisting of an ADC decrease in basal ganglia and white matter without major T2/fluid‐attenuated inversion recovery (FLAIR) injury may be a key finding in the acute phase of the disease in favour of a vasculitis hypothesis. These reversible lesions were associated with a good neurological outcome. These results call for further evaluation of the potential role of eculizumab in the choice of treatment for severe D+HUS, particularly in the case of early neurological signs.